1996
DOI: 10.1002/j.1550-8528.1996.tb00253.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Body Mass Index to Reproductive Factors in Pre‐ and Postmenopausal African‐American Women With and Without Breast Cancer

Abstract: The relationship of body mass index to reproductive factors in pre-and postmenopausal AfricanAmerican women with and without breast cancer. Obes Res. 1996;4:451-456. To date, there are virtually no existing data on the relationship between obesity, menopausal status, and breast cancer in African-Americans. Therefore, the present study was designed to test the following hypotheses in an African-American population: (1) there exists a positive association between BMI and breast cancer among postmenopausal women;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…13). Hospital-based case-control studies yielded conflicting results (10)(11)(12) + . Another possibility for the lack of association of obesity and weight gain with overall risk of postmenopausal breast cancer is that the strong and lasting effect of body size at age 18 years makes it difficult to detect an effect of weight gain and high BMI at later ages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13). Hospital-based case-control studies yielded conflicting results (10)(11)(12) + . Another possibility for the lack of association of obesity and weight gain with overall risk of postmenopausal breast cancer is that the strong and lasting effect of body size at age 18 years makes it difficult to detect an effect of weight gain and high BMI at later ages.…”
Section: Discussionmentioning
confidence: 99%
“…Several case-control studies have reported on the relation of obesity to breast cancer risk in African American women separately by menopausal status, with inconsistent results (10)(11)(12)(13)(14). There was little evidence of an association of current body mass index (BMI) with risk of breast cancer in premenopausal women (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 The association has been reported to persist even into postmenopausal age both in Caucasian-Americans 50 and in African-American women. 53 Teenage obesity in Western girls is associated with an increased prevalence of menstrual irregularity, both long and short cycles, and a tendency to anovulation. 54 Teenage obesity is also associated with an increased likelihood of irregular menstrual cycles continuing into adult life.…”
Section: Nutrition Obesity and Insulin Resistancementioning
confidence: 99%
“…Many studies of premenopausal cancer in African American women find no association with obesity status near the time of diagnosis (7). Among post-menopausal Black women, results have been mixed (7): some studies found decreased risk (8, 9), others increased risk (10, 11), and others found suggestive or null relationships (12, 13). …”
Section: Introductionmentioning
confidence: 99%